2016
DOI: 10.1097/eja.0000000000000367
|View full text |Cite
|
Sign up to set email alerts
|

McGRATH MAC video laryngoscope for insertion of a transoesophageal echocardiography probe

Abstract: BACKGROUNDTransoesophageal echocardiography (TOE) probe insertion in anaesthetised patients can cause pharyngeal and oesophageal injuries. Kim et al. have shown that insertion assisted by a Macintosh laryngoscope can reduce such complications but it may sometimes be difficult to observe the passage of a TOE probe. The McGRATH MAC (McGRATH) has been shown to provide a better view of the glottis, piriform fossa and oesophageal inlet during tracheal intubation than the Macintosh.OBJECTIVEWe hypothesised that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
(28 reference statements)
0
16
0
1
Order By: Relevance
“…The use of insertion aids, such as a laryngoscope, may reduce the incidence of oropharyngeal mucosal injury, odynophagia and the number of insertion attempts . The risk of complications may be further reduced by the use of a videolaryngoscope as the oesophageal inlet may be better visualised, however, there is little evidence yet to support this suggestion . Finally, we argue there should be more focus on teaching and sharing safe probe insertion techniques.…”
Section: Discussionmentioning
confidence: 92%
“…The use of insertion aids, such as a laryngoscope, may reduce the incidence of oropharyngeal mucosal injury, odynophagia and the number of insertion attempts . The risk of complications may be further reduced by the use of a videolaryngoscope as the oesophageal inlet may be better visualised, however, there is little evidence yet to support this suggestion . Finally, we argue there should be more focus on teaching and sharing safe probe insertion techniques.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, it has been reported that McG decreased the incidence of pharyngolaryngeal complications associated with the insertion of a transesophageal echocardiography probe. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Videolaryngoscopy can be particularly useful for guiding and correcting malposition of different devices through oropharynx such as nasogastric or orogastric tube [49], esophagoscopes, gastroscopes, or transesophageal echocardiography probe [50]. In addition, it can be useful when placing throat packs in oral and maxillofacial surgery.…”
Section: Insertion Of Different Devices Into Oropharynxmentioning
confidence: 99%